2023
DOI: 10.1097/mlr.0000000000001815
|View full text |Cite
|
Sign up to set email alerts
|

Health-care–Related Practices in Virtual Behavioral Health Treatment for Major Depression Before and During the COVID-19 Pandemic

Abstract: Background: The abrupt shift to virtual care at the onset of the COVID-19 pandemic had the potential to disrupt care practices in virtual behavioral health encounters. We examined changes over time in virtual behavioral health-care-related practices for patient encounters with diagnoses of major depression. Methods: This retrospective cohort study utilized electronic health record data from 3 integrated health care systems. Inverse probability of treatment weighting was used to adjust for covariates across 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…: These datasets represent additional visit details, including ancillary services orders and fulfillments, for clinical conditions selected for focused study on variation in provider ordering behavior, and patient fulfillment behavior, for related ancillary services: NBP, UTI, and DEP. [10][11][12][13] Further details of each of the CDM datasets are presented in the Supplement (Tables S4-S9, Supplemental Digital Content 1, http://links.lww.com/MLR/C605). Key decisions that informed contents of specific CDM datasets are summarized in the Supplement (Table S10, Supplemental Digital Content 1, http://links.lww.com/MLR/C605).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…: These datasets represent additional visit details, including ancillary services orders and fulfillments, for clinical conditions selected for focused study on variation in provider ordering behavior, and patient fulfillment behavior, for related ancillary services: NBP, UTI, and DEP. [10][11][12][13] Further details of each of the CDM datasets are presented in the Supplement (Tables S4-S9, Supplemental Digital Content 1, http://links.lww.com/MLR/C605). Key decisions that informed contents of specific CDM datasets are summarized in the Supplement (Table S10, Supplemental Digital Content 1, http://links.lww.com/MLR/C605).…”
Section: Resultsmentioning
confidence: 99%
“…This dataset is primarily sourced through HealthConnect tables. VV_ENC_NBP_DB, etc. : These datasets represent additional visit details, including ancillary services orders and fulfillments, for clinical conditions selected for focused study on variation in provider ordering behavior, and patient fulfillment behavior, for related ancillary services: NBP, UTI, and DEP 10–13 …”
Section: Resultsmentioning
confidence: 99%
“…Racial-ethnic disparities in telemedicine use were found within KP; adults identifying as Black, Asian, or Hispanic were less likely to use virtual care 6. The KP research studies also tackle new areas in telemedicine research by comparing the impact of telemedicine and in-person visits on ancillary services utilization, including medication, laboratories, and imaging, for urinary tract infections7 neck and back pain,8 and depression 9. These studies found that although ancillary service orders resulting from telemedicine visits were generally high, orders from telemedicine encounters were not placed as often as in-person encounters for urinary tract infections, 7 neck and back pain, 8 but there were no significant changes in patient fulfillment of ordered antidepressant medications 9.…”
Section: Commentarymentioning
confidence: 99%
“…The KP research studies also tackle new areas in telemedicine research by comparing the impact of telemedicine and in-person visits on ancillary services utilization, including medication, laboratories, and imaging, for urinary tract infections7 neck and back pain,8 and depression 9. These studies found that although ancillary service orders resulting from telemedicine visits were generally high, orders from telemedicine encounters were not placed as often as in-person encounters for urinary tract infections, 7 neck and back pain, 8 but there were no significant changes in patient fulfillment of ordered antidepressant medications 9. The KP findings highlight the importance of prior use of mail-order pharmacy options in promoting the fulfillment of prescribed medication orders, irrespective of visit mode 10.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation